Current status of hemostatic agents, their mechanism of action, and future directions. (March 2023) - Gupta, Ritvesh; Mohanty, Sibanwita; Verma, Devendra
The bleeding problem might seem straightforward, but it involves a plethora of complex biochemical pathways and responses. Hemorrhage control remains one of the leading causes of "preventable deaths" worldwide. The past few decades have seen a wide range of biomaterials and their derivatives targeted to serve as hemostatic agents, but none can be deemed as an ideal solution. In this review, we have highlighted the current diversity in hemostatic agents and their modalities. We have enclosed a comprehensive outlook of the proposed solutions and their clinical performance so far. In addition to these, several promising compositions are still in their infancy or developmental phases. The inclusion of novel upcoming nanocomposites has further widened the potencies of existing formulations as well.